The Relationship of Intimate Partner Violence With Psychiatric Disorders and Severity of Pain Among Female Patients With Fibromyalgia - Nermin GÜNDÜZ,; Erkal ERZİNCAN,; Aslıhan POLAT, (Archives of Rheumatology, 2019)
Objectives: This study aims to compare the prevalence of intimate partner violence and comorbid psychiatric disorders among patients with fibromyalgia syndrome (FMS) and healthy controls and also to investigate the relationship of intimate partner violence with psychiatric disorders and severity of pain in FMS patients. Patients and methods: The study group consisted of 136 females including 68 patients with FMS (mean age 43±10.4 years; range, 25 to 70 years) and 68 FMS-free healthy females (mean age 38.5±11.3 years; range, 22 to 70 years). Following a Structured Clinical Interview for Diagnostic and Statistical Manual-IV Axis I Disorders by a psychiatrist experienced in psychological trauma, Hamilton Depression Rating Scale (HDRS), Hamilton Anxiety Rating Scale (HARS), Visual Analog Scale (VAS) for the severity of pain and Domestic Violence Against Women Scale (DVAWS) were applied. Results: In FMS group, 85% of the patients were diagnosed with mood or anxiety disorder. Almost half of these patients had major depressive disorder. The total scores of DVAWS and all subscales were significantly higher in the FMS group than in the control group (p<0.01). The severity of domestic violence were related to the presence of any psychiatric disorder only in FMS patients (p<0.01). Almost half of the FMS patients with high DVAWS score had comorbid mood and anxiety disorders. There was a significant positive correlation between the total scores of DVAWS, HDRS, HARS, and VAS (p<0.01). Conclusion: Although the etiology of FMS is still uncertain, psychosocial factors may play role as risk factors. Therefore, a multidisciplinary approach to the treatment should be considered.